Rationale and design of the EMPERIAL‐Preserved and EMPERIAL‐Reduced trials of empagliflozin in patients with chronic heart failure. (19th June 2019) - Abraham, William T.; Ponikowski, Piotr; Brueckmann, Martina; Zeller, Cordula; Macesic, Hemani; Peil, Barbara; Brun, Michèle; Ustyugova, Anastasia; Jamal, Waheed; Salsali, Afshin; Lindenfeld, JoAnn; Anker, Stefan D.; et al.
Abstract : Aims: Heart failure (HF) is associated with considerable symptom burden and impairment in physical functioning and quality of life. The sodium–glucose co‐transporter 2 inhibitor empagliflozin reduced the risk of HF hospitalisation and cardiovascular death in patients with type 2 diabetes and established cardiovascular disease in the EMPA‐REG OUTCOME trial, and could potentially improve congestion symptoms and exercise capacity in patients with HF. We describe the designs of the EMPERIAL‐Preserved and EMPERIAL‐Reduced trials of empagliflozin in patients with chronic stable HF, with or without type 2 diabetes. Methods: EMPERIAL‐Preserved and EMPERIAL‐Reduced are randomised, placebo‐controlled trials designed to investigate the effects of empagliflozin on exercise capacity and patient‐reported outcomes in patients with chronic stable HF with preserved ejection fraction [HFpEF; left ventricular ejection fraction (LVEF) > 40%] and HF with reduced ejection fraction (HFrEF; LVEF ≤ 40%), respectively. In each trial, approximately 300 patients will be randomised 1:1 to receive empagliflozin 10 mg or placebo once daily for 12 weeks. In both trials, the primary endpoint is the change from baseline in 6‐min walk test distance at week 12. Key secondary endpoints are the change from baseline in Kansas City Cardiomyopathy Questionnaire total symptom score and change from baseline in dyspnoea score of the Chronic Heart Failure Questionnaire at week 12. Conclusion: The EMPERIAL‐Preserved and EMPERIAL‐Reduced trials will determine the effects of empagliflozin on exercise capacity and patient‐reported outcomes in patients with HFpEF and HFrEF, respectively, and provide insight into the potential of empagliflozin in the treatment of patients with HF. Clinical Trial Registration:ClinicalTrials.gov ID: NCT03448406 (EMPERIAL‐Preserved), NCT03448419 (EMPERIAL‐Reduced).